Ecological and social dimensions of ecosystem restoration in the nordic countries - Hagen, Dagmar; Svavarsdottir, Kristin; Nilsson, Christer; Tolvanen, Anne K; Raulund-Rasmussen, Karsten; Aradottir, Asa L; Fosaa, Anna Maria; Halldorsson, Gudmundur (Ecology and Society, 2013)
An international overview of the extent and type of ecological restoration can offer new perspectives for understanding, planning, and implementation. The Nordic countries, with a great range of natural conditions but historically similar social and political structures, provide an opportunity to compare restoration approaches and efforts across borders. The aim of this study was to explore variation in ecological restoration using the Nordic countries as an example. We used recent national assessments and expert evaluations of ecological restoration. Restoration efforts differed among countries: forest and peatland restoration was most common in Finland, freshwater restoration was most common in Sweden, restoration of natural heathlands and grasslands was most common in Iceland, restoration of natural and semi-cultural heathlands was most common in Norway, and restoration of cultural ecosystems, mainly abandoned agricultural land, was most common in Denmark. Ecological restoration currently does not occur on the Faroe Islands. Economic incentives influence ecological restoration and depend on laws and policies in each country. Our analyses suggest that habitat types determine the methods of ecological restoration, whereas socio-economic drivers are more important for the decisions concerning the timing and location of restoration. To improve the understanding, planning, and implementation of ecological restoration, we advocate increased cooperation and knowledge sharing across disciplines and among countries, both in the Nordic countries and internationally. An obvious advantage of such cooperation is that a wider range of experiences from different habitats and different socio-economic conditions becomes available and thus provides a more solid basis for developing practical solutions for restoration methods and policies.